Phenotype of p53 wild-type epitope-specific T cells in the circulation of patients with head and neck cancer - Albers, Andreas E. (Sci Rep, 2018)
CD8(+) cytotoxic T-cell (CTL) specific for non-mutated, wild type (wt) sequence p53 peptides derived from wt or mutant p53 molecules expressed in head and neck squamous cell carcinomas (HNSCC) have been detected in the circulation of patients with this disease. The frequency and differentiation/maturation phenotypes of these anti-tumor specific CTL can reflect the host’s immunologic response. Therefore, we investigated the frequency and phenotypes of wt sequence p53 peptide-specific CTL in patients with HNSCC (n = 33) by flow cytometric analysis using HLA-A*0201 tetrameric peptides (tet) complexed with the wt sequence p53(264–272) or p53(149–157) peptide and co-staining with phenotypic markers. One main finding was that increasing frequencies of tet(+) CD8(+) T cells in patients’ circulation correlated with increased frequencies of inactive naïve tet(+) cells, while those with effector memory and terminally differentiated phenotypes, which are associated with positive anti-tumor immune responses, decreased. We also found that the frequency of circulating tet(+) CD8(+) T cells negatively correlated with p53 expression in tumor tissues and tumor stage. Our findings support further clinical-based investigations to define the frequencies and phenotypes of wt sequence p53 peptide-specific CD8(+) T cells to predict disease severity, enhance selection of patients for inclusion in vaccination trials and highlight prerequisites to enhance immune susceptibility by activation of inactive naïve tet(+) T cells and/or enhancing circulating effector T cell activity by checkpoint blockage.